معوقات تطبيق الإدارة الإلكترونية فى المدارس الأهلية بمدينة الرياض من وجهة نظر مديرى المدارس - الوزارة، عبدالله بن محمد (جامعة الأزهر - كلية التربية, 2012)
This study Aims to study the application of electronic administration at private schools in Riyadh from the perspective schoolmasters. It also aims to find out the obstacles facing the application of electronic administration at these schools, in order to come up with suggestions that may help to apply electronic administration. Using descriptive survey research methodology, the researcher used a questionnaire to collect the date from (170) schoolmasters that represent (40%) of the population. The study findings include: The study sample agrees to some extent that the electronic administration is applied at private schools in Riyadh. The study sample also strongly agrees that there are obstacles that hinder the application of electronic administration in these schools. The study sample also strongly agrees to a group of suggestions that may help to apply electronic administration in these schools, including empowering schoolmasters with more administrative and financial authority, expanding training programs related to electronic administration, and increasing the budget for technological projects. Based on these findings, the researcher suggested a number of recommendations.
هدفت هذه الدراسة إلى تحديد واقع تطبيق الإدارة الإلكترونية في المدارس الأهلية بمدينة الرياض وذلك من وجهة نظر مديري المدارس. وكذلك التعرف على أبرز معوقات تطبيق الإدارة الإلكترونية في هذه المدارس، للوصول إلى مقترحات تساعد على تطبيق الإدارة الإلكترونية. واستخدم الباحث منهج البحث الوصفي التحليلي لتطبيق الدراسة على عينة بلغ عددهم (170) مديرا يمثلون (40%) من مجتمع الدراسة. وقد استخدم الباحث استبانة كأداة لجمع البيانات. وتوصلت الدراسة لعدد من النتائج من أهمها: أن أفراد الدراسة يرون أن تطبيق الإدارة إلكترونية يتم إلى حد ما في المدارس الأهلية بمدينة الرياض. كما أنهم موافقون بشدة على وجود معوقات تحد من تطبيق الإدارة الإلكترونية في المدارس في هذه المدارس. وأظهرت النتائج أن أفراد الدراسة موافقون بشدة مجموعة المقترحات التي تساعد على تطبيق الإدارة الإلكترونية في المدارس الأهلية بمدينة الرياض. ومنها دعم مديري المدارس بصلاحيات مالية وإدارية، وتكثيف البرامج التدريبية في مجال الإدارة الإلكترونية، والتوسع في الميزانية بما يحقق المشاريع التقنية. وبناء على ما توصلت إليه الدراسة من نتائج، قدم الباحث عددا من التوصيات لتحسين واقع تطبيق الإدارة الإلكترونية في المدارس الأهلية بمدينة الرياض.
Keywords: الإدارة الإلكترونية -- المدارس الأهلية -- مديرو المدارس -- الادارة المدرسية -- مدينة الرياض -- السعودية